2018
DOI: 10.1002/jsfa.9426
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of antioxidant egg‐chalaza hydrolysates against chronic alcohol consumption‐induced liver steatosis in mice

Abstract: BACKGROUND: Reactive oxygen species (ROS) overproduction is highly related to some human chronic diseases. There are approximately 400 metric tons of chalazae produced yearly after the processing of the liquid-egg production, which are disposed of as waste. The objectives of this study were to look for the optimal production condition of antioxidant crude chalaza hydrolysates and evaluate the in vivo antioxidant capacity via a chronic alcohol consumption mouse model. RESULTS: Antioxidant crude chalaza hydrolys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 34 publications
2
14
0
Order By: Relevance
“…Sun et al [ 50 ] formerly informed that hydrolysates from corn gluten meal that were rich in BCAAs lowered the AST and ALT activities in an acute alcoholism model. Consistent with these results, previous studies reported that animal-derived protein hydrolysates reduced the serum AST and ALT levels as well as the macro-lipid droplets and TG levels in the liver of chronic alcohol-fed mice [ 48 , 51 ].…”
Section: Discussionsupporting
confidence: 84%
“…Sun et al [ 50 ] formerly informed that hydrolysates from corn gluten meal that were rich in BCAAs lowered the AST and ALT activities in an acute alcoholism model. Consistent with these results, previous studies reported that animal-derived protein hydrolysates reduced the serum AST and ALT levels as well as the macro-lipid droplets and TG levels in the liver of chronic alcohol-fed mice [ 48 , 51 ].…”
Section: Discussionsupporting
confidence: 84%
“…Chow diets (LabDiet 5001, PMI Nutrition International/Purina Mills LLC, Richmond, IN, USA) and distilled water were provided ad libitum for mice during the experimental period. According to our previous study, the administration of 100 mg CCH/kg BW/day could pose the hepatoprotective effects in C57BL/6 mice against chronic alcohol consumption ( Yang et al., 2019 ). Hence, dosages as 50, 100, and 200 mg CCH/kg BW/day for low, medium, and high dosages, respectively, were given to the DG-treated mice.…”
Section: Methodsmentioning
confidence: 99%
“…Within recent decades, bioactive effects of food-derived protein hydrolysates have been attracted an attention ( Chou et al., 2014 , Abeyrathne et al., 2015 , Lin et al., 2017 ). These protein hydrolysates obtained from plants or animals possess some or better beneficial bioactivities when compared with their parent proteins ( Kim et al., 2012 , Chou et al., 2014 , Yang et al., 2019 ). In Taiwan, approximately 7 billion chicken eggs are produced per year, and for the 6% market share of liquid egg industries ( Council of Agriculture, Executive Yuan, Taiwan 2015 ), it is estimated that about 400 ton chicken egg chalazae are produced in the liquid egg industry per year, which are regarded as byproducts and always abandoned.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the U.S. Food and Drug Administration (FDA) stated to ban the utilization of PHOs in processed food [16]. To meet the new requirements, an effective alternative of PHOs which could mimic the rheology and sensory features of the PHOs are the new challenges for food scientists [17][18][19][20][21]. Oleogelation, which uses the three-phase emulsion system to physically fabricate the artificial butter-like product, is a promising way to meet the increasing demand for healthier food.…”
Section: Introductionmentioning
confidence: 99%